Non-Stipulation of Security from Loss in Commanding Right and Forbidding Wrong - Ã™Â…Ã˜ÂÃ˜Â³Ã™Â†Ã›ÂŒ Ã˜Â¯Ã™Â‡ÃšÂ©Ã™Â„Ã˜Â§Ã™Â†Ã›ÂŒ, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯; Ã˜Â§Ã›ÂŒÃ˜Â²Ã˜Â¯Ã›ÂŒ Ã™ÂÃ˜Â±Ã˜Â¯, Ã˜Â¹Ã™Â„Ã›ÂŒ Ã˜Â§ÃšÂ©Ã˜Â¨Ã˜Â±; Ã™Â…Ã™Â†Ã˜ÂªÃ˜Â¸Ã˜Â±Ã›ÂŒ, Ã˜ÂµÃ˜Â§Ã™Â„Ã˜Â (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
In legal works, the obligatoriness of commanding right and forbidding wrong has become restricted to stipulatory realization including âsecurity against lossâ. The jurists believe that commanding right and forbidding wrong has âa suspended and conditional obligatorinessâ toward the stipulation of security from loss in such a way that when a depravity or loss follows commanding right and forbidding wrong, this obligatoriness does not have actuality and is voided. Having re-examined the issue, the writers consider the evidences of the generally accepted view as violable despite its enjoyment of âgreat publicityâ. Briefly put, the writers believe that commanding right and forbidding wrong as a legal obligation has âan absolute and non-suspended obligatorinessâ toward qualified condition.